Exploring A-level mathematics teachers’ teaching practices and use of technology - Azlina Mohd Kosnin; Kee Jiar Yeo; Chinghao Chua (Institute of Advanced Engineering and Science, 2022)
Student-centered teaching methods and technology are often viewed as effective tools to raise students’ performance and interest in mathematics learning. Limited research exists on discussion of teaching methods and the use of technology on the general certificate of education (GCE) A-level mathematics. The purpose of this qualitative research where data were collected using semi-structured interviews was to explore how A-level mathematics teachers used teaching methods and technology for the delivery of mathematics instruction. Convenience sampling was applied, the participants were seven A-level teachers from a private college in Johor, Malaysia. The gathered responses were analyzed using thematic analysis based on the approaches suggested by Braun and Clarke. The findings of this research reported that while mathematics teachers revealed they made some attempts in incorporating technology and student-centered teaching approaches to their classes, traditional teaching approaches such as chalk-and-talk and drill-and-practices remained to be the dominant teaching approaches they would use in their classes. In order to have a closer examination between the relationship of students’ interest and students’ performance in mathematics, the researcher suggests the future direction of study on the development of a teaching module which serves as a reference guide to alleviate the mentioned teachers’ concerns.